Production of castings from silumins with nanostructural hypoeutectic silicon - E. I. Marukovich; V. Ju. Stetsenko; S. L. Radjko (Литьë и металлургия, 2003)
There is shown the principle possibility of the silumins casting with nanostructural eutectic crystals of silicon.